Analisis Dampak Pembangunan Arena Olahraga Terhadap Lingkungan di Kompleks Olahraga Manunggal Jati Semarang (Indonesian Journal for Physical Education and Sport, 2020)
The development of the sports arena in Indonesia is currently being intensified so that it can improve the sports activities and achievements of athletes, one of it is the Manunggal Jati Sports Complex. This study was using survey method with data collection technique was Likert 1 to 4 questionnaire. Using 4 indicators, namely ecological indicators, health indicators, socio-cultural indicators, and economic indicators. The data analysis used descriptive quantitative methods with percentage calculations. The population was all residents who live Â± 100 meters from the Manunggal Jati Sports Complex and the sample was 35 people, the technique using the mixed methods sampling technique. The results of the study, as a whole, showed that there are environmental impacts felt by the community towards a better direction due to the construction of the sports arena in the Manunggal Jati Sports Complex Semarang as much as 64.08%. From these sub-indicators, 20 sub-indicators showed a change in the environment towards a better direction, and as many as 3 sub-indicators have not shown changes for the better. Thus, it can be said that the construction of the sports arena in the Mangunggal Jati Sports Complex Semarang has an impact on the environment towards better environment.